Expressive Acts In Scoob! 2020 Movie : Pragmatics Study - Sevina Aulia; Puspita Sari (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2024)
This research focused on identifying and analyzing the expressive speech acts found in the movie "Scoob!" by Tony Cervone. The study utilized the theory of speech acts proposed by Searle in (Dey, 2023) and examined the types and purposes of expressive illocutionary acts in the movie. The findings revealed that the expressive acts contains 3 congratulating with (4%), 12 thanking with (16%), 37 praising with (49%), 15 greeting with (20%) and 8 apologizing with (11%), were present in the dialogue of the characters. Among these acts, praising was the most frequently observed, followed by thanking, greeting, apologizing, and congratulating. The purpose of these expressive acts varied, with thanking expressing gratitude, praising showing admiration, greeting welcoming someone, congratulating displaying empathy, and apologizing expressing regret. Overall, this research contributes to the understanding of expressive speech acts in cinematic contexts, particularly in the movie "Scoob!" by Tony Cervone.